2018
DOI: 10.1016/j.ijmedinf.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

The impact of three discharge coding methods on the accuracy of diagnostic coding and hospital reimbursement for inpatient medical care

Abstract: The accuracy of diagnosis codes and percentage of correct HRGs improved when coders used either case notes or medical support in addition to the discharge summary. Further emphasis needs to be placed on improving the standard of information recorded in discharge summaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
(26 reference statements)
0
18
0
Order By: Relevance
“…The Read codes seemed to suggest the opposite problem; there are a large number of codes for recording a CF condition, suspected or otherwise but given the wide choice, a simple CF diagnosis code was often chosen. The use of coding systems in a consistent manner and the limitations apparent in some coding systems, is a recognised concern in the use of EHR [10,30] and the reasons for the misclassified cases seemed consistent with this concern.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The Read codes seemed to suggest the opposite problem; there are a large number of codes for recording a CF condition, suspected or otherwise but given the wide choice, a simple CF diagnosis code was often chosen. The use of coding systems in a consistent manner and the limitations apparent in some coding systems, is a recognised concern in the use of EHR [10,30] and the reasons for the misclassified cases seemed consistent with this concern.…”
Section: Discussionmentioning
confidence: 93%
“…Whilst there is considerable value to be gained from the use of routine EHR for research, it also poses a number of challenges [9][10][11][12]. These can occur because routine EHR rely on data collected for administrative purposes rather than clinical research, so identifying clinical outcomes or decisions can be more difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Tsopra et al suggested that if the data needed to summarize patient discharge by specialist physicians were based on patient records, reports, and patient notes, it could reduce hospital costs by 1.8-16.5 million pounds (27); nonetheless, the results of different studies may not actually be comparable. Overall, it seems that the accuracy of the diagnostic codes or the errors in diagnostic coding in nine educational hospitals affiliated to Shahid Beheshti University of Medical Sciences is not significantly different from other studies.…”
Section: Discussionmentioning
confidence: 99%
“… 18 The application of machine learning in EHR is of great value. First, predictive modelling with EHR data can save labour, enhance efficiency, increase accuracy 19 , 20 and promote personalized medicine. 21 Second, machine-learning techniques can transform a large amount of textual information and unstructured data from patient records into structured data.…”
Section: Artificial Intelligence and Electronic Health Recordsmentioning
confidence: 99%